The Effectiveness of Corporate Communication and its Relationship to Job Performance in Media Institutions: A Survey Study in Sharjah Broadcasting Authority for the Period June 25, 2020 to September 25, 2020 - Ishag, Khalid Ibrahim Abdelaziz (Al-Adab Journal, 2021)
The research addressed the effectiveness of corporate communication and its relationship to job performance in media institutions, a survey in Sharjah Broadcasting Authority. The research aimed to identify the corporate communication means and channels of information flow in the organization structure of media institutions. The researcher used descriptive methodology and questionnaire as an essential tool for collecting information. Some of the important results of the research are: The employees in media institutions they use technical means in transferring instructions and directions as email, social media, and intranet, while there is no use of fax as technical means in media institutions. Media institutions have a comprehensive information and data system who achieves its goals. In addition, the management of media institutions it is interest with communicating information and decisions to all the different administrative levels that facilitates the nature of the work. There is no statistically significant relationship between the downward communication and the exerted effort in performing work for employees in media institutions. The study recommended providing adequate opportunity for employees in media institutions to transfer information to senior management, which is the upward communication that confirms that the lower levels in the organizational structure are not only a future of information, but also a source of information that is represented in opinions, trends and motivations.